Evaluation studies of persimmon plant (Diospyros kaki) for physiological benefits and bioaccessibility of antioxidants by in vitro simulated gastrointestinal digestion. (1st January 2017) - Martínez-Las Heras, Ruth; Pinazo, Alicia; Heredia, Ana; Andrés, Ana
Highlights: Antioxidants of kaki leaf infusion present the highest vulnerability to digestion. Higher bioaccessibility of antioxidant compounds from solid than liquid kaki matrices. Intestinal digestion enhances polyphenols bioaccessibility of kaki fruit and fibres. Abstract: This study aims to analyze the antioxidant benefits from persimmon leaf tea, fruit and fibres taking into account their changes along gastrointestinal digestion. The evolution of polyphenols, flavonoids and antioxidant capacity was studied using the recent harmonized in vitro protocol published by Minekus et al. (2014). The digestion was performed with and without digestive enzymes. Results showed aqueous leaf extract was richer in antioxidants than the fruit or the extracted fibres. Nevertheless, persimmon-leaf antioxidants were more sensitive to the digestive environment. In general, the oral conditions greatly affected the antioxidants, while gastric digestion led to slight additional losses. The intestinal step enhanced polyphenols and flavonoids solubility coming from the fruit and fibres. Additionally, the presence of digestive enzymes positively contributed to antioxidant release throughout digestion. Finally, the bioaccessibility of polyphenols, flavonoids and antioxidant activity of persimmon fruit were 1.4, 1.0 and 3.8 times higher than in aqueous leaf extract.